How does re-classification of variants of unknown significance (VUS) impact the management of patients at risk for hereditary breast cancer? - Ava Kwong; Cecilia Yuen Sze Ho; Vivian Yvonne Shin; Chun Hang Au; Tsun-Leung Chan; Edmond Shiu Kwan Ma (BMC, 2022)
Abstract Background The popularity of multigene testing increases the probability of identifying variants of uncertain significance (VUS). While accurate variant interpretation enables clinicians to be better informed of the genetic risk of their patients, currently, there is a lack of consensus management guidelines for clinicians on VUS. Methods Among the BRCA1 and BRCA2 mutations screening in 3,544 subjects, 236 unique variants (BRCA1: 86; BRCA2: 150) identified in 459 patients were being reviewed. These variants consist of 231 VUS and 5 likely benign variants at the initial classification. Results The variants in 31.8% (146/459) patients were reclassified during the review, which involved 26 unique variants (11.0%). Also, 31 probands (6.8%) and their family members were offered high-risk surveillance and related management after these variants were reclassified to pathogenic or likely pathogenic. At the same time, 69 probands (15%) had their VUS downgraded to cancer risk equivalent to the general population level. Conclusion A review of archival variants from BRCA1 and BRCA2 genetic testing changed the management for 31.8% of the families due to increased or reduced risk. We encourage regular updates of variant databases, reference to normal population and collaboration between research laboratories on functional studies to define the clinical significances of VUS better.